The influence of shoe on posture and performance of rifle shooters - A comparative study - Kim, S. E. (International Journal of Engineering Research and Technology, 2019)
Shooting sports includes different disciplines: rifle, handguns, and shotguns. This sports activity requires accuracy, precision, consistency, and speed. Various factors influence the performance of any shooters. This study considered the influence of shoe on the rifle shooters performance. In this comparative study, four female middle school rifle shooter with more than two years of rifle shooting experience have participated. Foot plantar pressure and center of pressure (COP) were measured using commercially available insole sensors and compared in two conditions (shooting with or without the shoe). The results were: the mean force at left foot interface was increased by 7.23 N (1.7 %), and the mean force at right foot interface was significantly (p < 0.05) increased by 32.87 N (12.9 %) after shooting with shoe compared without wearing the shoe. There was 0.716 mm (66.7 %) significant (p < 0.01) in COP distance in the right foot while shooting with the shoe. The lateral body moved enhanced while shooting with the shoe, which increased the shooter's stability and balance. These results confirm that wearing the shoe in rifle shooting sport could increase the stability and balance, which lead to an improvement in aiming and performance of shooters.